Sindrom metabolik pada remaja obes: prevalensi dan hubungannya dengan kualitas diet - Fillah Fithra Dieny; Nurmasari Widyastuti; Deny Yudi Fitranti (Jurnal Gizi Klinik Indonesia, 2015)
Background: The increasing prevalence of adolescents obesity in the last decade have an impact on the increased prevalence of adolescents metabolic syndrome (MetS). Diet quality is one of the determining factors in the incidence of adolescents obesity, so it can also be a factor for MetS.Objective: To analyze the relationship between diet quality and MetS risk factors in obese adolescents.Method: A cross-sectional study was conducted on the 57 obese students in 7th and 8th grades of Nasima and Kesatrian Junior High School in Semarang. Blood pressure (BP) and waist circumference (WC) measurements, as well as blood samples for measurement of fasting blood glucose (FBG), triglyceride (TG) and HDL cholesterol (HDL-C), were conducted to determine the number of risk factors experienced by the subject. Diet quality was measured through assessment of food consumption using a food frequency questionnaire (FFQ). Pearson and Spearman's test was used to determine the correlation between diet quality and MetS risk factors.Results: The majority of obese adolescents (96.5%) had a low-quality of diet. There were 31.6% subjects experienced pre-metabolic syndrome and 68.4% had MetS, with the prevalence of MetS, was higher in male subjects. The diet quality, variety, adequacy scores and fiber intake of the pre-metabolic syndrome group were higher than MetS group. Variety and adequacy scores had significant negative correlation with TG (r = -0.374, p=0.004; r = -0.357, p=0.006, respectively). There was no significant relationship between diet quality score and the number of MetS risk factors (p=0.538), although they had a negative correlation (r = -0.083).Conclusion: Prevalence of pre-metabolic syndrome and MetS was 31.6% and 68.4%. Though there was no significant relationship, diet quality had a negative correlation with the number of MetS risk factors. Variety and adequacy scores had a significant relationship with triglyceride levels.